The Synergistic Effect of Penicillin G and Sutherlandia frutescens [Syn. Lessertia frutescens] (Fabaceae) against Enterococcus faecalis - Nsele , Nhlanhla Wiseman; Thembane , Nokukhanya (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
The emergence of antibiotic-resistant bacteria is a growing concern in the field of medicine. This has led to the need for alternative treatments for bacterial infections. Antibiotic resistance occurs when bacteria evolve and develop mechanisms to survive and grow in the presence of antibiotics, rendering these drugs ineffective in treating infections. The study aimed to investigate the synergistic effect of a water-based extract of S. frutescens (a plant species) and penicillin G (an antibiotic) on the growth of E. faecalis. The objective was to determine if the combination of the plant extract and penicillin G could enhance the inhibitory effects on bacterial growth compared to penicillin G alone. The results of the study showed that the combination of the plant extract and penicillin G had a synergistic effect on inhibiting the growth of E. faecalis. This was evident from the significantly larger inhibition zone observed when compared to the use of penicillin G alone. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests also demonstrated that the combination was more effective against E. faecalis than penicillin G alone. A dilution of 1 in 4 of the combination resulted in 100% inhibition of bacterial growth. The study concludes that although the specific mechanism of action was not discussed, the results indicate that the combination of the plant extract and penicillin G may hold promise as an alternative treatment for antibiotic-resistant infections. However, further research is necessary to identify the active compounds present in the plant extract and to investigate the synergistic effects of the combination on other strains of bacteria. Understanding the mechanisms underlying the observed synergistic effects could help optimize and develop more effective treatment options against antibiotic-resistant bacteria.